2020
DOI: 10.1088/1361-6528/aba92a
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Bi doping in ZnO nanocrystals by co-doping with Al: crystal geometry calculations and photocatalytic activity

Abstract: In this work we demonstrate enhancement in visible-light photocatalytic activity (PCA) of ZnO nanoparticles (NPs) with minimal attenuation of visible light transmittance. This approach can benefit numerous optoelectronic and photocatalytic applications. ZnO NPs were p-n co-doped with Al and Bi to improve Bi doping into the ZnO crystal. Al- and/or Bi-doped ZnO was coprecipitated by ammonia from aqueous nitrate solutions of Zn2+, Al3+, and Bi3+, followed by microwave heating. Doping concentrations in Al- and Bi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The results indicate that the codoped ZnO electrode is capable of enhancing their sensitivity, in comparison to pristine ZnO [15]. There are studies where codoping, including aluminum and bismuth, led to an improvement in size and shape of the structures compared to the pure ZnO compound [16]. It has also been reported that doping involving lithium and dispersed rare earth oxides over the ZnO compact powders, improve the photoluminscence signal in ZnO, concluding that color depends on the Er 3+ , Tm 3+ , or Eu 3+ dispersed onto the ZnO pellets [17].…”
Section: Introductionmentioning
confidence: 91%
“…The results indicate that the codoped ZnO electrode is capable of enhancing their sensitivity, in comparison to pristine ZnO [15]. There are studies where codoping, including aluminum and bismuth, led to an improvement in size and shape of the structures compared to the pure ZnO compound [16]. It has also been reported that doping involving lithium and dispersed rare earth oxides over the ZnO compact powders, improve the photoluminscence signal in ZnO, concluding that color depends on the Er 3+ , Tm 3+ , or Eu 3+ dispersed onto the ZnO pellets [17].…”
Section: Introductionmentioning
confidence: 91%
“…126 However, there is no related report about the Bi-doped HPNCs applied in photocatalysis so far even though Bi-doping has been proven an effective way to modify traditional photocatalysts. [141][142][143] In addition to Bi, other trivalent metal dopings such as In 3+ and Au 3+ may also be promising metals in photocatalysis, and deserve the attention of photocatalysis researchers. 78,144 Metal-doped HPNCs hold great potential in photocatalytic applications, but the inferior efficiency still restricts their practical application.…”
Section: Bi-dopingmentioning
confidence: 99%